Meta-Analysis: The Effect of Anxiety During Pregnancy on the Risk of Premature Birth and Low Birth Weight in Infants - Suparno, Amalia Ulfah; Budihastuti, Uki Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2021)
Background: Pregnancy can be defined as the process of meeting spermatozoa with the ovum which is followed by attachment of the embryo to the uterine wall, in the process of pregnancy according to some or almost all women it becomes a happy process or causes anxiety due to the occurrence of many physiological and psychological changes, so that if it is not treated seriously then will have an impact on the baby such as premature birth and low birth weight. This study aims to estimate the magnitude of the effect of anxiety during pregnancy on premature birth and low birth weight with a meta-analysis study. Subjects and Method: This was a meta-analysis and systematic review conducted with PRISMA flow diagrams. Population= pregnant women, Intervention= anxiety, Comparison= not anxious, Outcomes= premature birth and low birth weight. Search articles through journal databases include: Google Scholar, PubMed, Science Direct. The articles used in this study are articles that have been published from 2000-2021. The keywords to search for articles were as follows: “antenatal anxiety” OR “pregnancy anxiety” OR “anxiety during pregnancy” OR “anxiety disorder” OR anxiety OR pregnancy AND “Perinatal outcomes” OR “adverse birth outcome” OR “neonatal outcome” OR “low birth weight” OR “Low Birth Weight” AND “preterm birth” OR “preterm infant”. The inclusion criteria were full text with a cohort study design, articles in English, analysis used multivariate with adjusted odds ratio. Eligible articles were analyzed using the Revman5 application. Results: 10 observational studies showed that anxiety during pregnancy increased the risk of preterm delivery by 1.49 times compared with no anxiety (aOR=1.49; 95% CI 1.33 to 1.66; p<0.001). A meta-analysis of 7 observational studies showed that anxiety during pregnancy increased the risk of low birth weight by 1.55 times compared with no anxiety (aOR=1.55; 95% CI 1.26 to 1.91; p<0.001). Conclusion: Anxiety during pregnancy increases the risk of premature birth and low birth weight.